2021
DOI: 10.1021/acscatal.1c01519
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Role of Metal Nanoparticles in Selectivity Control over Photodehydrogenative Coupling of Primary Amines to Imines and Secondary Amines

Abstract: Metal nanoparticles (NPs) are heavily involved in photocatalytic transformations to manipulate charge separation and storage, yet the catalytic role of metal NPs in tuning the selectivity of photoreactions is rarely addressed. Here, the photodehydrogenative coupling of primary amines is selected as the model reaction to probe the catalytic role of Pt and Pd NPs supported on graphitic carbon nitride (Pt/C 3 N 4 and Pd/C 3 N 4 ). When Pt/C 3 N 4 is employed as the photocatalyst, imine is produced via dehydrogena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 41 publications
1
44
0
Order By: Relevance
“…As we can see, the dominant peaks located at 73.7° and 70.6° can be assigned to Pt 0 , indicating the Pt species exist in metal. 45 However, with the increase of roasting temperature, the binding energy of Pt are significantly shift from 73.7 to 74.0 eV, suggesting the interaction between Pt and CN support are enhanced. In addition, it can be seen from the literature review, Pt 2+ belongs to soft acids and pyridine nitrogen is borderline bases.…”
Section: Resultsmentioning
confidence: 99%
“…As we can see, the dominant peaks located at 73.7° and 70.6° can be assigned to Pt 0 , indicating the Pt species exist in metal. 45 However, with the increase of roasting temperature, the binding energy of Pt are significantly shift from 73.7 to 74.0 eV, suggesting the interaction between Pt and CN support are enhanced. In addition, it can be seen from the literature review, Pt 2+ belongs to soft acids and pyridine nitrogen is borderline bases.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the Cu-N 3 site can effectively capture oxygen and initiate the subsequent activation reaction of oxygen molecules. To verify this result, the O 2 temperature-programmed desorption (O 2 -TPD) experiments were carried out. The desorption peak area represented the amount of oxygen adsorbed per unit catalyst mass, and the desorption temperature estimated the surface interaction strength of oxygen. As shown in Figure c, we can observe a higher desorption peak for Cu-N 3 , which indicated that more O 2 was desorbed on its surface.…”
Section: Resultsmentioning
confidence: 99%
“…Mono-, bi-, and poly-metallic nanoparticles (MNPs), or nanoalloys (NAs), find a wealth of potential uses across disciplines ranging from sensing 1,2 to drug-delivery, 3 memory-storage 4,5 to optics 6,7 . Among the most prominent applications, MNPs further play a significant role as thermal, [8][9][10] electro-chemical, 11,12 and photo-chemical 13,14 catalysts.…”
Section: Introductionmentioning
confidence: 99%